Getting Hammered: The Use of Experimental Archaeology to Interpret Wear on Late Bronze Age Hammers and Modern replicas - E. Giovanna Fregni (EXARC Journal)
Metalsmithing tools such as hammers are rarely recognised for their significance in understanding prehistoric metalworking technology. Their development and specialisation signal new metalworking techniques and a wider array of the types of metal objects being made. Our knowledge of ancient metalworking is further enhanced by examining the wear on these tools. The various scratches and dents all provide insight as to how the tool was used by smiths and in some cases can aid in the interpretation of metalworking activities relating to specific tasks (Fregni 2014).